Economic Voices from the Margins: Peasants and Working Classes in Historical Perspective - Supriya S. Belavi (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This study examines the economic experiences of peasants and workers under colonial and early post-colonial regimes, highlighting their often-marginalized role in shaping economic structures. Colonial policies prioritized surplus extraction and export-oriented production, impoverishing rural producers and creating exploitative labor systems that shaped enduring inequalities. Peasants faced cash-crop cultivation, heavy taxation, and forced labor, while industrial workers endured low wages and insecure conditions. Agrarian uprisings, including Indian satyagraha’s and African women’s protests, reflected collective resistance rooted in subsistence rights. Post-independence land reforms and industrial policies aimed at equity were unevenly implemented, leaving structural disparities. Drawing on economic history and development perspectives, the paper underscores how peasants and workers contributed labor, resistance, and transformation while remaining constrained by colonial legacies.